KECERDASAN AGRARIS: REINTERPRETASI KEJADIAN 1:26-30; 2:15 DARI PERSPEKTIF TEOLOGI AGRARIA - Andri Saputra, Jefri (Balai Diklat Keagamaan Jakarta, 2024)
Abstract This article aims to respond to agrarian issues that are currently struggling with churches and society in several regions in Indonesia. The texts of Genesis 1:28-30 and Genesis 2:15 often raise problems with ecological implications because of their contrasting meanings. Mastering and subduing creation in Genesis 1:28-30 tends to be counter-ecological, while Genesis 2:15 is pro-ecological. The author examines these two texts from the perspective of Norman Wirzba's Agrarian theology. The research results show that these two texts meet in efforts to manage natural potential and protect its vulnerability from damage. Genesis 1:28-30 constructs intelligent mastery or comprehensive and balanced insight into creation, and Genesis 2:15 constructs the act of cultivating natural potential and protecting its vulnerabilities from damage. These two texts are the starting point for constructing church services in responding to agrarian issues. Abstrak Artikel ini bertujuan untuk merespons isu agraria yang menjadi pergumulan gereja dan masyarakat masa kini di beberapa daerah di Indonesia. Teks Kejadian 1:28-30 dan Kejadian 2:15 kerap menimbulkan masalah implikasi ekologis karena maknanya yang kontras. Menguasai dan menaklukkan ciptaan dalam Kejadian 1:28-30 cenderung kontra ekologi, sedangkan Kejadian 2:15 bersifat pro ekologi. Penulis mengkaji kedua teks ini dalam perspektif teologi Agraria dari Norman Wirzba. Hasil penelitian menunjukkan bahwa kedua teks ini berjumpa dalam upaya mengelola potensi alam dan melindungi kerentanannya dari kerusakan. Kejadian 1:28-30 mengonstruksikan penguasaan secara inteligensi atau wawasan komprehensif dan berimbang terhadap ciptaan, dan Kejadian 2:15 mengonstruksikan tindakan mengolah potensi alam dan melindungi kerentanannya dari kerusakan. Kedua teks ini menjadi titik tolak mengonstruksikan pelayanan gereja dalam merespons isu-isu agraria.